2006
DOI: 10.1007/s10834-006-9032-9
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Patterns of Chinese Elders: Evidence from A Survey in Wuhan, China

Abstract: The elderly population in China has grown since 1999. Many Chinese businesses have noticed this trend and began to focus on the Gray Market. The behavior of older Chinese consumers has significantly changed. Descriptions of their behavior in previous research need to be updated. This paper uses data from a survey conducted by the authors in China to investigate the current behavior of older consumers. Results show that older Chinese consumers (1) have similar consumption needs as younger adults; (2) display mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Households living in the east and those residing in municipalities spend the most on food ($2,000 and $2,500, respectively), which is related to the higher cost of living in East China. Age did not seem to affect household expenses, which is consistent with the results of Ying and Yao (2006). Using data collected in Wuhan, China, the authors concluded that there are no substantial differences in consumption between older and younger Chinese households.…”
Section: Expensessupporting
confidence: 78%
“…Households living in the east and those residing in municipalities spend the most on food ($2,000 and $2,500, respectively), which is related to the higher cost of living in East China. Age did not seem to affect household expenses, which is consistent with the results of Ying and Yao (2006). Using data collected in Wuhan, China, the authors concluded that there are no substantial differences in consumption between older and younger Chinese households.…”
Section: Expensessupporting
confidence: 78%
“…The concept of compensatory consumption provides theoretical insights into buying behavior of BOP consumers where they overspend on cosmetics and other products that are associated with status and gives precedence to satisfaction of aspirational needs over more basic needs. This behavior is commonly observed in low-income population in emerging economies (Banerjee andDuflo, 2007, Subrahmanyan andGomez-Arias, 2008;Van Kempen, 2007;Ying and Yao, 2006). Indian BOP households overspend on festivities and events like weddings with a desire to follow social norms and enhance the status (Viswanathan, 2007).…”
Section: Compensatory Consumptionmentioning
confidence: 89%
“…Even soft expressions such as “the golden age” and “the mature market” have all encountered criticism from older consumers (Mitchell 1996 ). Ying and Yao ( 2006 ) found that older consumers had similar consumption needs as younger adults. Therefore, treating those consumers with a younger self-perceived age the same way as younger consumers may be more beneficial for businesses.…”
Section: Self-perceived Age Of Older Chinese Consumersmentioning
confidence: 99%